Investigation of various types of biological corrosion of concrete - S. A. Loginova; A. A. Petrenko (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. Determination of the degree of development of various types of microorganisms and their effect on the physical and mechanical properties of concrete.Method. Assessment of the possibility of concrete to serve as a substrate for various types of biodestructors was carried out using the determination of moisture absorption and pH of water drawing of concrete samples.Result. Experimental mechanism of action of various microorganisms on concrete is established. Taxonomic composition of microorganisms most aggressive to concrete is determined. The impact of biofouling on the physical and mechanical properties of concrete was assessed.Conclusion. The results of the investigation serve as the basis for competent selection of the most effective methods of corrosion protection of concrete structures operating in biologically aggressive environments.